Creating demand for unmet needs: Agile Storytelling - Mehta, Jade; Long, Emily; Bynagari, Vidhur; Shojaei, Fereshtehossadat; Shojaei, Fatemehalsadat; O’Brien, Andrew R. W.; Boustani, Malaz (Frontiers in Health Services, 2024)
IntroductionThe translational gap from the discovery of evidence-based solutions to their implementation in healthcare delivery organizations derives from an incorrect assumption that the need for change among executive, administrative, or clinical personnel is the same as the demand for change. For sickle cell disease (SCD), implementation of evidence-based guidelines is often delayed or obstructed due to lack of demand. This challenge allows for the persistence of resource limitations and care delivery models that do not meet the community's unique needs. Agile Storytelling is a process built on the scientific foundations of behavioral economics, complexity science, and network science to create local demand for the implementation of evidence-based solutions.MethodsAgile Storytelling includes a design phase and a testing phase. The design phase converts the evidence-based solution into a minimally viable story of a hero, a villain, struggle, drama, and a resolution. The testing phase evaluates the effectiveness of the story via a series of storytelling sprints in the target local healthcare delivery organization. The efficacy of Agile Storytelling was tested in an iterative n-of-1 case study design.ResultsAgile Storytelling was used in a large, urban, healthcare system within the United States to facilitate implementation of national SCD best-practice guidelines. After repeated failures attempting to use national and local data regarding the high societal need to hire a SCD-specific social worker, an Agile change conductor using Agile Storytelling was able to create demand for the new position within a week. This decision has ultimately improved patient outcomes and led to the adoption of a specialized collaborative care team for SCD within the health network.DiscussionAgile Storytelling can lead to structured, effective, and informed storytelling to create local demand within healthcare delivery organizations.